Analysis of Revenue Accounting Information Systems at PT. Pusaka Sunny Jaya: Analisis Sistem Informasi Akuntansi Pendapatan Pada PT. Pusaka Sunny Jaya - Ferry Prima Wicaksana; Heri Widodo (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to analyze the income accounting information system that has been applied at PT. Sunny Jaya's heritage is in accordance with the theory of accounting information systems which in the future can be used as material for improving company systems. The method used in this research is descriptive method. Data collection methods used are observation, interviews, and documentation. The data analysis technique used is to analyze the income accounting information system at PT. Sunny Jaya's heirloom. Accounting information system at PT. In practice, the Sunny Jaya heritage has been going well because each part has been managed by each staff so that there is very little cheating that can be done. The use of the system in the company here as a whole has helped to meet reporting needs so that reports and inputs can be updated, besides that the use of programs/systems has provided good internal control.